1998
DOI: 10.5014/ajot.52.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Endocrine Activation During Pregnancy Alters Neurobehavioral State in Primate Infants

Abstract: The results demonstrate that neurobehavioral state alterations are found in infants from mothers with increased endocrine activity during pregnancy. Neurobehavioral state disorganization can have an adverse impact on the human infant's concurrent and subsequent occupational performance. These findings establish the usefulness of the nonhuman primate model for advancing knowledge on early contributions to the development of human infant occupational behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…This conclusion concurs with research showing that population variation in mother-infant interactions depends upon several characteristics, including maternal-typical behavior (Weaver, Richardson, Worlein, De Waal, & Laudenslager, 2004), infant temperament (Coe et al, 2010; Mantymaa et al, 2006; Roughton, Schneider, Bromley, & Coe, 1998) and environmental context (Ellis et al, 2012). Studies in rodents have revealed how variation in maternal care can have far-reaching consequences on emotional reactivity and brain development, which may continue to be manifest even in subsequent generations (Champagne & Meaney, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…This conclusion concurs with research showing that population variation in mother-infant interactions depends upon several characteristics, including maternal-typical behavior (Weaver, Richardson, Worlein, De Waal, & Laudenslager, 2004), infant temperament (Coe et al, 2010; Mantymaa et al, 2006; Roughton, Schneider, Bromley, & Coe, 1998) and environmental context (Ellis et al, 2012). Studies in rodents have revealed how variation in maternal care can have far-reaching consequences on emotional reactivity and brain development, which may continue to be manifest even in subsequent generations (Champagne & Meaney, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Prenatal stress affects cognitive abilities including operant discrimination [91] , reversal task in a water maze [92,93] and memory [94] . In other animal studies, maternal stress during pregnancy results in offspring that are more irritable, anxious and difficult to control [61,[95][96][97][98] .…”
Section: The Third Pathophysiology Of Cocaine: Fetal Programmingmentioning
confidence: 99%
“…That may be changing, however, as human research begins to translate the experimental animal findings showing that prenatal stress is a central paradigm for demonstrating long-term effects of prenatal exposures on behavioral and biological development (Coe et al, 2003; Maccari et al, 2003; Weinstock, 2005). Abundant animal work using the prenatal stress paradigm points to glucocorticoid exposure as a leading candidate mechanism (Maccari et al, 2003; Matthews, 2000; Roughton et al, 1998; Seckl & Holmes, 2007; Weinstock, 2005). The specific mechanisms of action underlying the programming effect are unconfirmed, but may include increased activation of the offspring HPA axis, alteration of glucocorticoid receptor sensitivity, and alteration of genetic expression in the stress response system.…”
mentioning
confidence: 99%